THE EFFECT OF THE IMPLEMENTATION OF E-SAMSAT, TAX SANCTIONS, AND INCOME ON THE COMPLIANCE OF MOTOR VEHICLE TAXPAYERS IN BADUNG REGENCY - Ni Made Ayu Tabita Cintya Hardi; Ni Ketut Lely Aryani Merkusiwati (INJOSEDU: International Journal of Social and Education, 2025)
The capital market serves as an important medium for investors to generate profits through. Tax is a mandatory contribution to the state, payable by individuals or entities, coercive in nature based on law, without direct compensation, and used to finance state expenditures for the greatest prosperity of the people. Taxpayer compliance reflects the extent to which taxpayers fulfill their tax obligations in accordance with the applicable laws and regulations. This study aims to examine the effect of the implementation of E-Samsat, tax sanctions, and income on the compliance of motor vehicle taxpayers in Badung Regency. This research employs a quantitative approach with a survey method through the distribution of online questionnaires using Google Forms. The number of respondents in this study was 100 people, selected using the accidental sampling method. The data analysis technique used was multiple linear regression analysis with the aid of IBM SPSS version 25. The analysis results show that E-Samsat has a positive and significant effect on taxpayer compliance, tax sanctions have a positive and significant effect on taxpayer compliance, and income has a positive and significant effect on taxpayer compliance. These findings support Attribution Theory and Task Technology Fit Theory, and provide practical input for relevant agencies, particularly the Samsat Office in Badung Regency, in improving taxpayer compliance.